Between Culture and Safety: The Paradox of Protecting Domestic Violence Victims in Mediation at the Batusangkar Religious Court, Indonesia - Irma Suryani; Arifki Budia Warman; Alfi Husni; Andiko; Revalina Fathiya Azzahra (Nusantara: Journal of Law Studies, 2026)
Mediation is a mandatory procedural step in divorce cases before Indonesian religious courts, yet its effectiveness remains contested, particularly in cases involving domestic violence. This study examines the implementation of mediation and the incorporation of local wisdom in domestic violence-based divorce cases at the Batusangkar Religious Court, a socio-legal context shaped by Minangkabau society's matrilineal culture. Employing an empirical legal approach with qualitative methods, data were collected through in-depth interviews with judges, mediators, and disputing parties, non-participant observation of mediation sessions, and document analysis. The data were analysed using the Miles and Huberman interactive model, including data reduction, display, and verification. The findings reveal that mediation practices function as pragmatic adaptations to socio-economic and institutional constraints, often conducted in a single, time-compressed session and oriented toward managing post-divorce rights rather than reconciliation. The incorporation of local wisdom occurs implicitly through cultural expressions and moral narratives, while formal adat actors, such as ninik mamak, are excluded due to regulatory limitations and concerns about victim protection. An interplay of structural rigidity, cultural values, institutional capacity, psychological dynamics, and mediator competence shapes mediation effectiveness. This study contributes academically by advancing the discourse on legal pluralism through the concept of “functional coexistence” between state law and adat, and by theorising mediation as a form of street-level bureaucracy in religious courts. It also enriches socio-legal scholarship by integrating trauma-sensitive and culturally informed perspectives into mediation studies, offering a nuanced model for handling domestic violence cases in plural legal systems.